2019
DOI: 10.1039/c9ra02078k
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diagnostic methods for diabetes mellitus from tear fluid

Abstract: In our pilot study we assessed the diagnostic potential of FS, IRS and AFM for diabetes mellitus using tear fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…The evaporation of biofluids shows different induced patterns according to the process of self-organization during evaporation, which may be a significant improvement in the diagnosis and detection of diseases. These biofluids include blood serum [ 1 , 8 , 9 , 10 , 11 ], whole blood [ 12 , 13 , 14 ], and tear fluid [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaporation of biofluids shows different induced patterns according to the process of self-organization during evaporation, which may be a significant improvement in the diagnosis and detection of diseases. These biofluids include blood serum [ 1 , 8 , 9 , 10 , 11 ], whole blood [ 12 , 13 , 14 ], and tear fluid [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, although many studies demonstrated the diagnostic potential of SFS, 32–35 tear fluid was analyzed by this method only in two studies. Glinská et al 11 studied tear fluid of diabetic patients with different treatments and length of the disease. They analyzed the shifts and fluorescence intensity of synchronous fluorescent spectral signal located at λ ex /Δ λ ≈ 280/50 nm between patients with different treatment and length of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been constantly and consistently used for the study of tear uid in various diseases and were helpful in better understanding the disease molecular mechanisms. [11][12][13] Moreover, they have the potential not only to make the regular examinations faster and easier but might capture the initial pathological changes in glaucomatous patients.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic analysis of tear fluid has been used for diagnostic purposes in many studies in the case of ocular diseases which are characterized by loss of tear production, e.g., glaucoma [ 4 ], dry eye syndrome (DES) [ 5 ], and systemic diseases, such as diabetes mellitus [ 6 ], major depressive disorder [ 7 ], or even cancer [ 8 , 9 ]. For identifying changed content of tear fluid, researchers use various methods.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an appropriate analytical method that characterizes its composition without separation procedures but is sensitive to changes caused by pathological conditions is crucial. Three-dimensional fluorescence analysis in the form of constant wavelength synchronous spectra (CW) shows enormous potential [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%